An Exploratory Study on Usage and Impact of Information Technology on the SMES Performance of Jammu Region - Chahal, Hardeep; Kohli, Ruchi (Indian Journal of Marketing, 2008)
The espousal of information technology is indispensable in the era of global competitive economy for the competitive advantage. The study addresses the extent of usage of Information Technology (IT) and its impact on the performance of business enterprises operating in Jammu industrial clusters. The relevant data was collected through structured questionnaire from 20 SMEs. On the basis of study results, the four distinct stages through which firms appeared to pass during the adoption of IT were identified. The firms in the first stage found to adopt IT tools, with focus on data processing using office automation tools & e-mails; the second stage firms in addition to first stage IT tools, were found to develop websites for promotional purposes; the third stage firms were using websites to communicate electronically with their business trading partners&customers and the last, fourth stage firms were using advance e-commerce software’s like Enterprise Resource Planning (ERP) and Electronic Data Interchange (EDI). Overall, the study found that espousal of technology is low in Jammu SMEs, as majority of them are falling in infancy stage.